Valuing Solar Subsidies - Bryan Bollinger; Kenneth Gillingham; A. Justin Kirkpatrick (CESifo GmbH, 2025)
Individuals trade present for future consumption across a range of economic behaviors, and this tradeoff may differ across socioeconomic groups. To assess these tradeoffs, we estimate a dynamic model of residential solar adoption and system sizing in California using household-level data on solar irradiance, electricity consumption, and electricity rates that offer plausibly exogenous variation in the future benefits from adopting relative to upfront costs. We find implicit discount rates of 15.3%, 13.8%, and 10.0% for low-, medium-, and high-wealth households. Counterfactual simulations demonstrate opportunities to reduce the regressivity of solar adoption, increase policy cost-effectiveness, and improve welfare for low-wealth households.
Keywords: L94; Q48; H23; D12; 330; solar; discount rates; energy policy; distributional impacts; dynamic discrete choice models